2018
DOI: 10.1016/j.mtla.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic origin of stress overshoots and serrations in a CuZr metallic glass

Abstract: In this work we use molecular dynamics simulations to study the stress overshoots of metallic glass Cu50Zr50 in three scenarios (unloading-reloading, slide-stop-slide, and stress serrations) that are associated with shear band relaxation. We found that, after the elastic recovery effect is factored out, atomic volume in the shear band barely changes during compressive relaxation but decreases during tensile relaxation, while local fivefold symmetry increases consistently for both cases. We propose that the ato… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…These results are in agreement with recent MD simulation results which showed that a cyclic loading after the formation of a shear band in a Cu 50 Zr 50 HG leads to structural relaxation, and consequently, a stress increase occurs in the stress-strain curve (Tang et al, 2018). Experiments and theoretical models have shown that this phenomenon depends on temperature, strain rate, and structural relaxation (Kawamura et al, 1997;Lu et al, 2003;Maaß et al, 2012;Jiang et al, 2015;Yang et al, 2019).…”
Section: Stress Overshoot During Cyclic Loadingsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in agreement with recent MD simulation results which showed that a cyclic loading after the formation of a shear band in a Cu 50 Zr 50 HG leads to structural relaxation, and consequently, a stress increase occurs in the stress-strain curve (Tang et al, 2018). Experiments and theoretical models have shown that this phenomenon depends on temperature, strain rate, and structural relaxation (Kawamura et al, 1997;Lu et al, 2003;Maaß et al, 2012;Jiang et al, 2015;Yang et al, 2019).…”
Section: Stress Overshoot During Cyclic Loadingsupporting
confidence: 92%
“…MD simulations were carried out using the LAMMPS simulation package (Plimpton, 1995).The interatomic interactions are described by the Finnis-Sinclair-modified-type potential for Cu-Zr (Mendelev et al, 2009) and the embedded atom model potential for Pd-Si (Ding et al, 2012). These potentials have been optimized to predict accurately the structure of liquid and amorphous Cu-Zr and Pd-Si alloys and were successfully applied to Cu-Zr and Pd-Si glasses (Cheng et al, 2013;An et al, 2016;Tang et al, 2018;Adjaoud and Albe, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the recently reported ∆T up to 2 K is comparable to our lowest simulated ∆T (∼20 K) when considering the sliding velocity difference. Although flow stress serrations are beyond the capacity of MD simulations [37], some insightful comments can be made here. As mentioned above, ∆T is limited by the elastic energy released during the shearing process.…”
Section: Discussionmentioning
confidence: 99%